Crystal structure of catena-poly[[silver(I)-{μ-2,6-bis[(1H-pyrazol-1-yl)methyl]pyridine-κ3N1,N2:N2′}] nitrate] - Daeyoung Kim (Acta Crystallographica Section E: Crystallographic Communications, 2015)
In the title complex, {[Ag(C13H13N5)]NO3}n, the AgI atom is coordinated by three N atoms from two bidentate/monodentate pyrazolylpyridyl ligands to form a distorted trigonal–planar geometry [range of angles: 83.34 (6) (chelate ring) to 139.15 (7) °]. The chelate ring has a distorted boat conformation. The dihedral angle between the pyridyl ring and the coordinating pyrazolyl ring is 67.22 (6)°. The non-coordinating pyrazolyl ring is twisted by 62.97 (7)° from the pyridyl ring. In the crystal, the complex cations are arranged in polymeric chains along the c-axis direction, with the nitrate counter-anions situated in between. Weak C—H...O hydrogen bonds link the ions into a three-dimensional network.